2017
DOI: 10.1128/jcm.01766-16
|View full text |Cite
|
Sign up to set email alerts
|

Combined Testing for Chlamydia, Gonorrhea, and Trichomonas by Use of the BD Max CT/GC/TV Assay with Genitourinary Specimen Types

Abstract: The BD Max CT/GC/TV (MAX) assay is a true multiplex assay for simultaneous detection of chlamydia (CT), gonorrhea (GC), and trichomonas (TV). We evaluated assay performance for women using endocervical and vaginal swabs as well as urine specimens. A total of 1,143 women were tested for CT, GC, and TV and, subsequently, another 847 (1,990 total women) for CT and GC only, with positivity rates for CT, GC, and TV of 7.1%, 2.3%, and 13.5%, respectively. In men, the performance for CT and GC was determined using on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
(26 reference statements)
1
39
0
1
Order By: Relevance
“…Numerous studies have shown that multiplex real‐time PCR assays were sensitive and useful modality for the diagnosis of STIs . Chung et al recently evaluated the performance of two commercial multiplex real‐time PCR assays including the GeneFinder assay for six STD pathogens and reported excellent agreement between the two assays ( κ = 0.87) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that multiplex real‐time PCR assays were sensitive and useful modality for the diagnosis of STIs . Chung et al recently evaluated the performance of two commercial multiplex real‐time PCR assays including the GeneFinder assay for six STD pathogens and reported excellent agreement between the two assays ( κ = 0.87) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that multiplex real-time PCR assays were sensitive and useful modality for the diagnosis of STIs. 5,8,9,11,13 Chung et al recently evaluated the performance of two commercial multiplex real-time PCR assays including the GeneFinder assay for six STD pathogens and reported excellent agreement between the two assays (κ = 0.87). 13 In the present study, there was excellent concordance between the results of the DiaPlexQ assay and the GeneFinder assay for each microorganism regardless of The main limitation of this study was the lack of a reference standard and the retrospective nature of the study.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35] In addition, several emerging nucleic acid amplification platforms combined with fully and partially automated instrumentation are available for targeting multiple microorganisms in a single test reaction. 12,14,30,36,37 However, these platforms are low throughput or have a high cost per sample, preventing rapid screening of large numbers of specimens. Compared to other diagnostic strategies, STI-MS using MALDI-TOF MS technologies are generally more reliable and can be more easily automated.…”
Section: Discussionmentioning
confidence: 99%
“…One possible cause for the higher number of discrepancies in the clinical specimens for causative agents of STIs may be due to target pathogens with a low concentration, as reported by Van et al in an evaluation of BD MAX assay. 37 Digital PCR has been successfully applied in the field of pathogen detection 46,47 and is particularly suited to the low-level detection of nucleic acid even with a highly complex background. 47,48 In the arbitration stage, ultrasensitive digital PCR was performed to resolve discordant results.…”
Section: Discussionmentioning
confidence: 99%